Comments about a recent publication entitled "Improving glass forming ability of off-eutectic metallic glass formers by manipulating primary crystallization reactions". (December 2021) - Tournier, Robert F.; Ojovan, Michael I.
Abstract: Comments about a recent publication entitled "Improving glass forming ability of off-eutectic metallic glass formers by manipulating primary crystallization reactions." 'Acta Materialia, 200 (2020) 710-719 by Y. Q. Zeng, J. S. Yu, Y. Tian, A. Hirata, T. Fujita, X. H. Zhang, N. Nishiyama, H. Kato, J. Q. Jiang, A. Inoue, M. W. Chen. The liquidus temperatures Tl of Ni60 Pd20 P20-y-x Siy Bx glass formers are equal to the disappearance temperatures Tn+ of liquid medium-range order resulting from the formation of an undercooled phase behind the glass phase. At this temperature, a volume fraction of about 15%, corresponding to the percolation threshold of configurons, melts accompanied by an endothermic enthalpy. Graphical abstrct: Image, graphical abstract